Karakterisasi morfologi, biokimia, dan uji enzimatis isolat khamir buah apel (Malus domestica Borkh.) yang berpotensi menghasilkan bioetanol - Hilmi Fadhli; Endang Kusdiyantini; Nurhayati Nurhayati (Jurnal Biologi Tropika, 2019)
Bioethanol can be produced by the fermentation using microorganisms such as yeast. The type of yeast that can produce bioethanol is still limited to certain yeast types such as Saccharomyces cerevisiae. Isolation and characterization of yeast need to be done to determine yeast isolates capable of producing bioethanol. Yeast can grow on a substrate that is rich in sugar as in the apple fruit. Enzymatic tests can support the ability to use on various substrates. This study aims to isolation, characterization, and enzymatic tests of yeast from apple that potential to produce bioethanol based on morphological and biochemical tests. The isolation method is done by using spread plates on PDA media. Morphological tests are carried out by making macroscopic (form, color, elevation, margin, the texture of colonies) and microscopic (form, budding, size of cells)observations of colonies and yeast cells. The growth was carried out on PDA at 6, 28, 37ᵒC, and also 50% glucose observed, Carbohydrate fermentation test (glucose, maltose, sucrose, lactose), and urease were used to the biochemicals characterization. Enzymatic tests were using amylase test, protease test, lipase test, and cellulase test. The bioethanol was measured bypycnometer method. The results of yeast isolation from apples were obtained 3 isolates, namely K1, K2, K3 with cell size 3,74 µm, 3,79 µm, and 3,41 µm respectively. Enzymatic test results showed that the presence of amylase enzyme activity in yeast. Based on morphological and biochemical characterization, K2 isolate was selected as genus Pichia sp. and able to producebioethanol by 5.6% (v / v).